Habituation-Based Religious Character Education Grounded in Pancasila: Evidence from a Juvenile Correctional Setting in Indonesia - Sri Sulistijaningsih; Encep Syarief Nurdin; Juntika Nurihsan; Muhammad Sabri (Badan Pembinaan Ideologi Pancasila, 2025)
The Reform Era of 1998, followed by rapid globalization and technological advancement, has profoundly affected the moral foundation of Indonesia’s younger generation. Data from the Indonesian Child Protection Commission (KPAI, 2022) show that West Java ranks highest in child protection cases, contributing to the increasing number of juvenile offenders at the Class II Juvenile Correctional Institution (LPKA) in Bandung, particularly in cases involving sexual misconduct. This situation demands a character development strategy that transcends administrative correction and focuses on moral and spiritual formation grounded in Pancasila, especially its first principle, Belief in the One and Only God. This study aims to design and evaluate a religious character development strategy using a habituation method implemented through supplementary classes. Employing a mixed-methods exploratory sequential design, the research began with qualitative data collection through observation, interviews, and document analysis, followed by quantitative analysis using pre-test and post-test data examined through the Wilcoxon Signed-Rank Test. The findings revealed that 29 out of 30 participants showed improved post-test scores, indicating significant positive changes in religious values, discipline, and spiritual awareness. These results confirm the effectiveness of the habituation-based strategy in fostering religious character and suggest that the model can be adopted by other juvenile correctional institutions to cultivate responsible, spiritually conscious youth with strong commitment to religious and national values.